Brain-adapted Leadership Effective Leadership according to Neuropsychological Findings - Hoffmann, Christoph (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2023)
The book shows you how you can effectively integrate the latest findings of neuroscience into your everyday work or leadership. Brain-adapted leadership shows you how applied psychology from the perspective of neuroscience works both in leadership work and in everyday professional life as a whole. Based on a neuropsychological behavioral model, you will learn about the plausible connections between perceptions, needs, emotions, thinking and acting. These insights form a valuable basis for leading yourself, teams and corporate units. In addition, you will receive numerous exercise instructions and examples for illustration and practical implementation. The subject of this work is of particular importance to you if you want to better understand your own feelings and behavior and those of your fellow human beings in order to achieve valuable interactions and fulfilling work activities. Target Audience: This reference book is aimed at managers and coaches, as well as people in the world of work who are willing to work on themselves to achieve greater satisfaction, serenity and balance: and neuroscience knows that we can do this, even into old age. About the author: Christoph Hoffmann is a graduate psychologist FH, graduate engineer HTL; studied psychology with a focus on Industrial and Organizational Psychology in Zurich. He has leadership experience in various adult education institutions and works at the IAP at the ZHAW Zurich University of Applied Sciences as a consultant and lecturer in the Centre for Leadership, Coaching and Change Management.
Foreword -- Preface -- 1. introduction -- I. Theoretical foundations for managers -- 2. applied neurobiology for managers -- 3. applied neuropsychology for managers -- II. human behaviour in the world of work -- 4. neuropsychological behavioural model -- III. brain-appropriate leadership -- 5. brain-appropriate self-leadership -- 6. brain-appropriate employee leadership -- 7. brain-appropriate corporate leadership -- 8. appendix -- 9. glossary.
Keywords: Psychology, Industrial; Management; Personnel management; Psychological consultation; Neuropsychology; School management and organization; School administration; Work and Organizational Psychology; Management; Human Resource Management; Consulting; Neuropsychology; Organization and Leadership